Development of Learning Tools Experiential Model Exploring the Surrounding Nature to Improve Generic Science Skills of Junior High School Students - Dania, Siti Evita Rhama; Taufiq, Muhamad (Universitas Negeri Semarang, 2021)
This study aims to analyze the feasibility and readability of the Experiential Model Exploring the Surrounding Nature (E-JAS) learning instrument. This type of research is development research which refers to the ADDIE development model. However, this research is limited to only using 4 stages of development, namely: Analysis, Design, Development, and Evaluation. This was due to the conditions and circumstances of the Covid-19 pandemic. Data collection techniques using the method of observation, documentation, and questionnaires. The data collection instruments used validation sheets, student and teacher readability questionnaires. The results of the research that have been done are: Validation of the syllabus obtained a score of 0.85. The validation of the learning implementation plan obtained a score of 0.78. Validation of student worksheets obtained a score of 0.85. The validation of the evaluation questions obtained a score of 0.86. The readability of students towards learning instruments is 80% in the good category and the readability of the teacher for learning devices is 83.4% in the very good category. It is concluded that the E-JAS learning instrument developed is declared very feasible with an average validation percentage of 0.83 and an average readability of 81.7% so it is very feasible to be used to support learning activities.